2019
DOI: 10.1016/j.adhoc.2019.101938
|View full text |Cite
|
Sign up to set email alerts
|

A primer on design aspects, recent advances, and challenges in cellular device-to-device communication

Abstract: Device-to-Device (D2D) communication is one of the technologies on the spotlight for enhancing the cellular network performance towards the fifth generation wireless systems. It has diverse potentials to cater for both critical and non-critical applications. For example, timely information dissemination can be achieved during disasters using D2D communication. Also, content sharing and real-time applications can be effectively facilitated. Recently, new applications and technologies are beginning to embrace D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 197 publications
0
8
0
Order By: Relevance
“…Power allocation is crucial in D2D communication technology over B5G networks [108]. DUs need an acceptable range of power levels to achieve optimal network performance and increase the data rate simultaneously [109]. In addition, there is a need to improve a device's transmission power since it can also raise link capacity [110].…”
Section: A Power Allocationmentioning
confidence: 99%
“…Power allocation is crucial in D2D communication technology over B5G networks [108]. DUs need an acceptable range of power levels to achieve optimal network performance and increase the data rate simultaneously [109]. In addition, there is a need to improve a device's transmission power since it can also raise link capacity [110].…”
Section: A Power Allocationmentioning
confidence: 99%
“…Various algorithms and approaches are applied in this concept. Amodu et al [10] describe the utilization and impact on multi-media data over device-to-device communication. The proposed methods improve the quality of service on both sides' primary users and device-to-device communication users.…”
Section: Related Workmentioning
confidence: 99%
“…The impact of intracell interference is very high and decreases the performance of networks [6][7][8]. Various authors and research scholars suggest that resource optimization is a better way to handle resource selection in sharing mode such as power control [9,10]. Various authors reported that the sharing of resources with a cellular network is a single-way communication.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to schemes involving hierarchical cooperation, although those schemes could be better than those considering simple multi-hop schemes in some situations, their implementations are much more complicated. More importantly, the implementation of simple multi-hop D2D communications in wireless networks is more plausible thanks to the recent developments in ad-hoc networks [57] and D2D networks [58], [59].…”
Section: A Related Literaturementioning
confidence: 99%